Evaluation of feed resources for local goat production under traditional management systems in Golomoti EPA Dedza and on-station at Bunda Campus, LUANAR, Malawi - Mkutche, C.D. (International Institute of Tropical Agriculture, 2020)
The on-station study was conducted at Sakhula, Bunda College (LUANAR), and on-farm in Golomoti Extension Planning Area (EPA). The objectives of the study were to assess constraints to goat production, to assess pre-weaning body weights of local Malawi goat kids, to analyze the nutrient content of selected tree and grass fodder species and to evaluate effect of feeding goats with Faidherbia albida pods and Gliricidia sepium based supplements on feed intake, growth rate and carcass quality. The results on constraints to goat production and pre-weaning body weights of local Malawi goat kids were based on a survey of 47 and 79 sample households, respectively. In Golomoti EPA, indigenous goat type was dominant (95.74%); natural grass formed a major feed resource (57.40%); the major disease was diarrhoea (59.6%). The majority of farmers (74.5%) had a shelter constructed for goats on the ground level and the main source of water was the river (91.5%) in wet season and (68.10%) in dry season. The on-farm flock monitoring study on birth weight, weekly body weight and pre-weaning average daily gain, used approximately 67 males and 56 females local goats owned by farmers, to evaluate the growth performance of kids grazing on natural forages with no supplementation. The study revealed that under farm condition, average birth weight of male and female local goat kids were; 3.11±0.04 and 2.49±0.05kg, with pre-weaning average daily gain (ADG) of 116.78±2.99 and 115.00±3.39 g/day, respectively. The diets used in the feeding study were; Diet 1= Grazing plus 410g maize bran (MB), Diet 2 = Grazing plus 405g Gliricidia sepium leaf hay plus 410g maize bran (GLM), Diet 3 = Grazing plus dry 405g Faidherbia albida pods plus 410g maize bran (FDM) and Diet 4 = Grazing plus 202.5g Gliricidia sepium leaf hay plus 202.5g dry Faidherbia albida pods plus 410g maize bran (GFM).